Children’s physical fitness and cognitive control in China: the moderating role of family support for physical activity - Fengling Zhang; Xiaoqi Wang; Kefu Peng; Lei Xu (BMC Public Health)
Abstract Objective This study aimed to explore the relationship between physical fitness and cognitive control in Chinese children, with a focus on gender differences and the moderating role of family support for physical activity (FSFPA). Method This study employed a cross-sectional design to assess 148 children aged 12–14 years from Guangzhou. Physical fitness was evaluated using the National Student Physical Fitness Standard, family support for physical activity (FSFPA) was measured with the validated Family Support for Physical Activity Scale, and cognitive control was assessed using the Stroop color-word task, Go/No-Go task, and task-cue paradigm. The statistical analyses included descriptive statistics, correlation analysis, and hierarchical regression analysis to examine the relationships between variables. Results Gender differences were observed in physical fitness and cognitive control. Girls scored higher in physical fitness and showed better accuracy in interference suppression, with faster reaction times in impulse control. BMI and speed were positively correlated with cognitive flexibility in both genders. For boys, cardiopulmonary endurance positively affected interference suppression, and muscle strength influenced impulse control. BMI and speed were linked to cognitive flexibility. For girls, speed, cardiopulmonary endurance, and muscle strength improved interference suppression, while BMI influenced cognitive flexibility. FSFPA moderated the relationship between physical fitness and cognitive control for both genders. It positively impacted interference suppression and cognitive flexibility for both boys and girls. Conclusion Physical fitness in Chinese children is positively associated with cognitive control, with gender-specific differences in the fitness components influencing cognitive outcomes. FSFPA significantly moderates this relationship, enhancing the positive effects of physical fitness on cognitive control. These findings suggest that promoting physical fitness, particularly through family-based physical activity support, may improve children’s cognitive control abilities.